Hubungan Kontrasepsi Suntik Depo Medroxy Progesteron Asetat (DMPA) Dengan Pertambahan Berat Badan Di Wilayah Kerja Puskesmas Kertak Hanyar Kabupaten Banjar Tahun 2017 - mukhtar mukhtar; Akhmad Rizani; Erni Setiawati (Jurnal Skala Kesehatan, 2021)
Hormonal contraception is the most preferred type of contraception for family planning acceptors, especially injection contraceptives. Kertak Hanyar Health Center Family Planning Service Coverage January - October 2016 found 58.82% of injection contraceptive acceptors. The most commonly used injection contraceptive method is Depo Medroxy Progesterone Acetate (DMPA). These contraceptives are highly effective in preventing pregnancy, but have the main side effect of changing body weight. This study aims to determine the relationship between Depo Medroxy Progesterone Acetate (DMPA) injection contraception with weight gain in the Kertak Hanyar Public Health Center, Banjar Regency in 2017. The research method used is an analytical survey with aapproach cross sectional. The number of samples in this study were 99 injection contraceptive acceptors with the sampling technique using purposive sampling. The research instrument used a family planning card (KB card), weight scales and interviews. Data analysis was performed using thetest Chi Square with a confidence level of 95%. The results of the study of 64 respondents who used DMPA injection contraceptives the most experienced excess weight gain, namely 26 respondents (41%) and of the 35 respondents who used combined injection contraceptives the most experienced normal weight gain, namely 22 respondents (62.9%). The results of statistical tests showed that there was a relationship between injection contraceptive DMPA and weight gain of r = 0.038 < a = 0.05. Keywords: DMPA Injectable Contraception, Weight Gain